Fashion by design - Ellinwood, Janice Greenberg (New York Fairchild Books, 2011)
"Fashion by Design covers the elements and principles of design as they relate to fashion. By exploring the best examples from early to contemporary fashion design, students will develop the eye of the fashion designer, able to identify and understand how to manipulate the elements and principles of design. The objective is for design students to use these guidelines not to simply develop an appreciation of aesthetics but to execute an aesthetically pleasing garment design. The theory of Fashion by Design originates in the field of art, while also drawing on aesthetics in the field of clothing and textiles"--Publisher's web site.
1. About design -- pt. 1. The Elements of design -- 2. Line -- 3. Form, shape and space -- 4. Texture and light -- 5. Pattern -- 6. Color and value -- 7. Color and industry -- pt. 2. The principles of design -- 8. Balance -- 9. Emphasis -- 10. Rhythm -- 11. Proportion -- 12. Unity.
Includes profiles of famous fashion designers providing insight into their artistic thinkiing and sources of inspiration: Madeleine Vionnet, Charles James, Claire McCardell, Chanel, Rudi Gernreich, Christian Dior, Rei Kawakubo, Issey Miyake, Yves St. Laurent, Mariano Fortuny, Gianni Versace, Roberto Capucci, Valentino Garavani, Vivienne Westwood, Hubert de Givenchy, Elsa Schiaparelli, Madame Gre?s, Yohji Yamamoto, and Jeanne Lanvin.
Keywords: Bauhaus -- Influence; Fashion design; Fashion designers